Criticism on Indonesia's water resource management - Gunawan, Adi; Pakendek, Adriana; Heryanti, Febrina (The International Journal of Politics and Sociology Research, 2023)
Water is one of the primary natural resources that the state should protect as a public good to avoid commercialism and capitalist efforts and acts. However, government policies on water resources management will lead to uncontrolled exploitation of water resources in the future. Therefore, this research aimed to analyse the water resources law and provide criticism of the regulation and impact on environmental life and the public goods economy. This research was library research that used normative legal research methods. Furthermore, this research also used secondary data and qualitative discussion. The findings showed that water resources management in Indonesia led to exploitation, commercialism and international-scale capitalism that would significantly endanger environmental conditions. This condition was exacerbated by the international organisations’ efforts that sought to control water resources in Indonesia.